Kinerja Lingkungan dan Tingkat Pengungkapan CSR Sebelum dan Sesudah UU No 47 Tahun 2012 - Fadli Andika Putra; Lindrianasari Lindrianasari (Jurnal Akuntansi dan Keuangan (JAK), 2018)
Environmental performance and disclosure level of CSR to the enactment of Law No.47 year 2012 is still voluntary. This means companies are not required to disclose environmental performance in the annual report. While in 2012 has been applied new law, then with enactment of the Act environmental performance should be disclosed in the annual report. This study aims to determine how much influence Law No. 47 year 2012 can improve the environmental performance and the level of CSR dsiclosure. There are two variables in this study, ie environmental performance as measured by ISO 14001 certification and CSR disclosure rate measured by GRI4. The number of sample of this study amounted to 640 companies of all companies listed on the BEI in 2008-2015. From the results of research on environmental performance and discloseure level of CSR, positively affect the implementation of Law No.47 year 2012.